Proses Pengangkatan Anak (Adopsi) dalam Perspektif Hukum Islam - Rina Budi Hartati; Muntaha Luthfi (AL-BURHAN, 2023)
This study aims to find out how the process of adopting children is carried out by the Muslim community in Plangitan Village, Pati District, Pati Regency. This study uses field research methods (field research). Research data were analyzed using descriptive-qualitative method. Data were collected by observation, interviews, and documentation which were analyzed using an interactive model. The results showed that: First, the process of adopting children carried out by the Muslim community in the Plangitan sub-district was not in accordance with the official procedure for adoption, namely that it was not carried out through a court decision process, in this case the authority of the Religious Courts. The average adopted child is taken from the relative environment of the adoptive parents. So that the community only adopts children in a familial manner because the adoption is almost the same as the relationship between foster parents and foster children; Second, that the legal consequence of the adoption process that is not in accordance with the law is that there is no legal certainty for both the father (adoptive parent) and the adopted child, as well as the absence of legal protection for the fate of the adopted child regarding their rights including the child's civil rights; Third, the adoption of children in the perspective of Islamic law in the Muslim community of the Plangitan sub-district there are those that are in accordance with Islamic law and some that are contrary to Islamic law. What is in accordance with Islamic law is that the adoptive parents do not change the lineage of the adopted child, while what is contrary to Islamic law is that the adoptive parents have changed the lineage of the adopted child to become their own biological child. In accordance with the concept of maqashid syari'ah or the concept of maslahah, adoption in the perspective of Islamic law in the Muslim community of the Plangitan sub-district should have the main objective of protecting offspring (hifdzu nasab).